Studies in molecular structure of plant polysaccharides : exudates from Encephalartos species - Vogt, Daphne Constance (Department of Chemistry, 2016)
This project forms part of a general programme in which the molecular structure of plant polysaccharides, particularly those that occur as gummy exudates from trees, are studied. Variations in the molecular structure of the polysaccharides are linked with the taxonomy of the plant concerned; this link with taxonomy is of particular interest where the cycads are concerned as these plants originated during the Mesozoic era and can therefore be considered as "living fossils". The exudate gums from six different species of the genus Encephalartos were surveyed, and the detailed molecular structures of the gums from two of the species, viz. E. friderici-guilielmi and E. longifolius were examined. Of particular interest in the gums from this genus is the glucuronomannoglycan core structure. The determination of the core structure is made particularly difficult in this case by its being surrounded by a complex structure of sugars and uronic acid residues.